Medical Students’ Perception about the Impact of Teachers’ Attitude on their Academic Performance and Character Building. - Saif, Marwa; Saif, Safa; Shahid, Noor; Anwar, Aiza; Kazmi, Tahseen (Journal of University College of Medicine and Dentistry, 2022)
Introduction: To observe the student’s perception about teacher’s attitude and its impact on academic performance and character building of the student. Methodology: A descriptive cross-sectional study using a random sampling technique was conducted among students from all the years of MBBS of Central Park Medical College, CMH Lahore Medical College & Institute of Dentistry, and Allama Iqbal Medical College in July- August 2021.The minimum sample size calculated from Raosoft sample size calculator was 314. The questionnaire consisted of questions sorted as students’ insight regarding teachers’ attitude and impact of that attitude on academics and on character building. Factor analysis and chi-square method was used to interpret the results. Results: Two hundred eleven female and one hundred three male students filled in the questionnaire. Approximately 74% of the students mentioned that negative attitude of the teacher decreased their academic performance and had a negative influence on their character building. Conclusion: There is a positive correlation between the attitude of a teacher and academic achievement of students as well as their character building. Positive attitude leads to higher achievement of the students whereas negative attitude deteriorates their progress and demotivates them.